Perception of English vowels by Javanese and Sundanese speakers; A mouse-tracking study - Perwitasari, Arum (UI Scholars Hub, 2018)
Second language (L2) learners often encounter difficulties caused by the interference of their native language (L1). The aim of this study is to examine how the Javanese and Sundanese vowel systems hinder the perception of ten English vowels. Thirty Javanese, thirty Sundanese, and twenty English native speakers participated in a mouse-tracking experiment. Participants were required to identify English vowels corresponding to an auditory token by clicking on one of two word strings presented on a computer screen. According to the Speech Learning Model (SLM) hypothesis, the Javanese and Sundanese speakers were predicted to have higher error rates and show a larger Area Under the Curve (AUC) for similar vowels (same IPA symbols, but different diacritics between L1 and the target vowels) than the native English speakers. For new vowels (no same IPA symbols found between L1 and the target vowels), the L2 speakers were predicted to have lower error rates and a smaller AUC than the native English speakers. According to the Second Language Linguistic Perception (L2LP), however, the prediction is stated in the reverse. Repeated measures of ANOVAs found that: 1) the Javanese and Sundanese speakers were less accurate in perceiving the new vowels /ɑː/, /ʌ/, /æ/, /ε/, /ɪ/, and /ʊ/ and similar vowels /iː/ and /uː/. 2) The Javanese speakers showed a larger AUC than native speakers for new vowels /ɑː/, /ɜː/, /ɔː/, and /ʌ/ and for similar vowels /iː/ and /uː/. The Sundanese speakers showed a greater attraction to the incorrect alternatives than the native speakers for new vowels /ɑː/, /ɜː/, /ɔː/, /ʌ/, /æ/, /ε/, /ɪ/, and /ʊ/ and similar vowels /iː/ and /uː/. Our findings partially support the L2LP hypothesis that the Javanese and Sundanese listeners are likely to show high error rates and a large attraction towards the incorrect alternatives of new vowels. The results confirmed that perceptual difficulties varied significantly according to the influence of L1 vowel inventories.